Aktywność inwestycyjna polskich przedsiębiorstw - Wolak-Tuzimek, Anna (Investment Activity of Polish Enterprises, 2008)
The paper presents the Polish enterprises investment activity while taking small and medium size enterprises into special consideration. The repartition of the investments has been made, and those which are profitable have been described. Basing on statistical data published by the Ministry of Economy and the Ministry of Finance and by the Polish Confederation of Private Employers Lewiatan, the analysis of mediocrity, dynamism, and structure of enterprises investments costs in the years 2000-2006 has been made. The principal limitation in small and medium size enterprise investment activity has been discussed and its financial sources have been indicated as well
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 597-606